Rickettsia infection in Amblyomma tonelliae, a tick species from the Amblyomma cajennense complex - Tarragona, Evelina Luisa (2015)
The present study was performed to evaluate the Rickettsia infection in Amblyomma tonelliae ticks from Argentina. All ticks were subjected to DNA extraction and tested by a battery of PCRs to amplify fragments of four rickettsial genes, 23S-5S, gltA, ompA and htrA. Two ticks were positive. The Rickettsia detected in one tick represents a new lineage which is named Rickettsia sp. strain El Tunal. This new strain belongs to the canadensis group because it is closely related to Rickettsia monteiroi, Rickettsia canadensis and Candidatus "Rickettsia tarasevichiae". They clustered together on a high supported clade with both gltA and htrA genes. The other positive tick was infected with Candidatus "Rickettsia amblyommii". The results presented in this study constitute the first records of Rickettsia infection in A. tonelliae ticks. However, the medical relevance of these findings should be considered cautiously because the pathogenicity of Rickettsia sp. strain El Tunal and Candidatus "R. amblyommii" remains undetermined.